Lecturer’s Room Monitoring System - Omar, Muhammad Syariefuddin; Tajul Azhar, Muhammad Syukri (2016)
The motivation for this project came from the idea of making it easier to find lecturer in their room. Students find it hard to meet their lecturer as their schedule may be differ from the students after class. They find out that their lecturer always not in their rooms which troubles the students as they need to meet with their lecturer to submit works, assignments, and to consult their lecturer. If the lecturers are not available, they need to keep going to monitor the lecturer availability. Lecturer’s Room Monitoring System project helps student to find their lecturers thus, making them easier to find them and safe time.